Closed-Form Expression for First Null Beamwidth of a Beam-Steered Dolph–Tschebysheff Array. Issue 1 (2nd January 2016) - Das, Tamal; Ghosh, Archit; Chatterjee, Soumyo; Chatterjee, Sayan
ABSTRACT: In this article, a closed-form expression for the first null beamwidth of a beam steered Dolph–Tschebysheff linear array antenna has been presented, where the number of elements, uniform inter-element spacing, side lobe level (in dB), and steering angle are considered as design parameters. Accordingly, the limitation in the beam-steering capability of a Dolph–Tschebysheff linear array has been modeled computationally. First null beamwidth values obtained using the proposed formula has been compared with that obtained from a conventional array factor plot. Results shows at least 95% accuracy in predicting the value of first null beamwidth and maximum steering angle under particular design constraints showing the effectiveness of the proposed formulas.